PERSEPSI SISWA TERHADAP KEGIATAN EKSTRAKURIKULER TARI DI SMA PERTIWI 1 PADANG - Citra Harseptiana; Fuji Astuti; Susmiarti Susmiarti (SENDRATASIK UNP, 2018)
Abstract This article aimed to determine students' perceptions of dance extracurricular activities at Pertiwi 1 High School Padang. The type of this research was descriptive research. This research was conducted at Pertiwi 1 High School Padang with 75 students participating in extracurricular activities. The populations of this research were students who took dance extracurricular activities; this study required 40 samples to represent 75 populations. Data collection techniques used in this study were questionnaires, observation, documentation, interviews and literature studies. The results showed that indicators about students' perceptions of dance extracurricular activities at Pertiwi 1 High School in Padang could be said well. Indicators of perceptions about student admission to dance extracurricular at Pertiwi 1 High School Padang with the level of achievement of respondents namely strongly agree (SS) 61.2%, agree (S) 28.3%, doubt (R) 7.2%, disagree (TS) 0.2% and strongly disagree (STS) 0%, an indicator of perceptions about students' understanding of dance extracurricular activities at Pertiwi 1 High School Padang with a high level of respondent strongly agree (SS) 60.6%, agree (S) 29, 3% hesitant (R) 9.3% disagree (TS) 0.2% and strongly disagree (STS) 0%, indicator of perceptions about students' assessment of dance extracurricular at Pertiwi 1 High School Padang with attainment level strongly agree ( SS) 60.4%, agree (S) 26.8%, doubt (R) 10%, disagree (TS) 1.8% and strongly disagree (ST) 0%. Keywords: Perception, Students, Extracurricular Dance